1969
DOI: 10.1002/zaac.19693640511
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer‐Spektren von Eisenphthalocyanin‐Komplexen

Abstract: Die Mössbauer‐Spektren des Eisen(II)‐phthalocyanins, FePc, der anionischen Komplexe des Typs [FePc]n− (n = 1, 2, 3, 4) und des Kations [FePc]+ wurden bei verschiedenen Temperaturen aufgenommen. Die Isomerieverschiebungen und Quadrupolaufspaltungen und ihre Temperaturabhängigkeit sind auf der Grundlage einer MO‐Behandlung der Komplexe interpretiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Such FeN 2+2 /CB structures were proposed by Charreteur et al as active sites. 48 Another possible configuration could be a second in-plane ferrous FeN 4 center, where iron occurs in the midspin state similar to the iron phthalocyanine published by Taube et al 49 At room temperature, they found values of δ iso ) 0.37 mm/s and E Q ) 2.58 mm/s.…”
Section: Interpretation Of 57mentioning
confidence: 67%
See 1 more Smart Citation
“…Such FeN 2+2 /CB structures were proposed by Charreteur et al as active sites. 48 Another possible configuration could be a second in-plane ferrous FeN 4 center, where iron occurs in the midspin state similar to the iron phthalocyanine published by Taube et al 49 At room temperature, they found values of δ iso ) 0.37 mm/s and E Q ) 2.58 mm/s.…”
Section: Interpretation Of 57mentioning
confidence: 67%
“…Next to Charreteur’s FeN 2+2 /CB site, the distances and positions of two adjacent graphene layers may vary. Following the correlation according to Taube, the effect could be explained by changes in the coordination in the vicinity of the center (nearest-neighbor effects), for example, by implementation of sulfur in the surrounding aromatic system leading to a distortion of the graphene like environment. Because it is known that the substituents in the periphery of a macrocyclic ring affect the physical and chemical properties of the metal center, these changes evoke deviations in Mössbauer patterns.…”
Section: Resultsmentioning
confidence: 99%
“…26,28,50 The doublet D2 has Mössbauer parameters similar to those of crystalline iron phthalocyanine (FePc). 51 In its crystalline form, both the square planar nitrogen coordination as well as interactions with nitrogen atoms in the axial direction (from FePc molecules on top or below) contribute to the quadrupole splitting, which is much larger than other Fe(II)N 4 sites with intermediate spin. We assume that a similar pseudo-sixfold coordination of D2 is exclusively realized inside the material and inhibits its contribution to the catalytic activity.…”
Section: Characterization Of Pyrolysed Cmpmentioning
confidence: 99%
“…Caughey, et al,u have also reported that no zero-field splitting for [Fe(DTP)]2G could be detected in the range 0 < D < 28 cm-1; hence we do not anticipate any dipolar contribution to the isotropic shifts. Assuming then that the observed shifts are contact shifts, eq 1 yields upon substitution of the Boltzmann expression and McConnell's contact shift equation23 v --K/T^ciiXi + vT (3) where K = gß'\eßky vtl, xt S¿St + 1 )nte+'^T ß+^…”
Section: Resultsmentioning
confidence: 99%